Participation of the Delegation of the Serbian Church in the Election of the Russian Patriarch in 1945 and the Arrival of the Russian Church in Yugoslavia - Fajfrić, Boris Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
After the death of the Russian patriarch Sergius, preparations for the election of a new patriarch began immediately, in which the government of the Soviet Union provided ample assistance. Unlike the last election, in which Sergius had been elected through the Synod and several bishops because of warfare, this time it was planned for the election assembly to be held in full presence of all the bishops, priests, and lay people. It was also planned to invite the heads of other Orthodox churches, including the Serbian Orthodox Church. As Patriarch Gavrilo was prevented from responding to the summons, as he was in captivity and nothing was known about him, his then deputy metropolitan of Skopje, Josif Cvijović, and the bishop of Niš, Jovan Ilić, went to the assembly. At that time, they witnessed the strengthening of the Russian Church, with the help of the state.
Keywords: Russian patriarch; convocation; Serbian church; Soviet Union; Serbian Orthodox Church